Crystal optics for precision x-ray spectroscopy on highly charged ions—conception and proof. (28th May 2015) - Beyer, H F; Gassner, T; Trassinelli, M; Heß, R; Spillmann, U; Banaś, D; Blumenhagen, K-H; Bosch, F; Brandau, C; Chen, W; Dimopoulou, Chr; Förster, E; et al.
Abstract: The experimental investigation of quantum-electrodydamic contributions to the binding energies of inner shells of highly charged heavy ions requires an accurate spectroscopy in the region of hard x-rays suitable at a limited source strength. For this purpose the focusing compensated asymmetric Laue crystal optics has been developed and a twin-spectrometer assembly has been built and commissioned at the experimental storage ring of the GSI Helmholtzzentrum Darmstadt. We characterize the crystal optics and demonstrate the usefulness of the instrumentation for accurate spectroscopy of both stationary and fast moving x-ray sources. The experimental procedures discussed here may also be applied for other spectroscopic studies where a transition from conventional germanium x-ray detectors to crystal spectrometers seems too demanding because of low source intensity.